1993
DOI: 10.1152/ajpcell.1993.264.5.c1180
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exercise alters contractility and morphology of isolated rat cardiac myocytes

Abstract: Chronic exercise training elicits positive adaptations in cardiac contractile function and ventricular dimension. The potential contribution of single myocyte morphological and functional adaptations to these global responses to training was determined in this study. Left ventricular cardiac myocytes were isolated from the hearts of sedentary control (Sed) or exercise-trained (TR) rats. Training elicited an approximately 5% increase in resting myocyte length (Sed, 121.0 +/- 2.0 vs. TR, 126.7 +/- 2.0 microns; P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
83
1
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 18 publications
17
83
1
2
Order By: Relevance
“…We found that training alone elicited a small (ϳ6%) but significant increase in cell length. This type of adaptation is similar to that previously described in younger healthy rat models of training (31,36). The fact that LWR did not increase with training indicates that the longitudinal cardiocyte growth was also accompanied by cross-sectional myocyte growth.…”
Section: Discussionsupporting
confidence: 88%
“…We found that training alone elicited a small (ϳ6%) but significant increase in cell length. This type of adaptation is similar to that previously described in younger healthy rat models of training (31,36). The fact that LWR did not increase with training indicates that the longitudinal cardiocyte growth was also accompanied by cross-sectional myocyte growth.…”
Section: Discussionsupporting
confidence: 88%
“…Both cell length and width increased, whereas only lengthening was observed in rats (29,42). No differences in cardiomyocyte dimension between the sexes were found, even though males had greater ventricle mass, which may suggest a higher number of cardiomyocytes in males.…”
Section: Discussionmentioning
confidence: 79%
“…Until recently, findings appeared somewhat contradictory. Treadmill running with fixed exercise intensity induced only minor increments in ventricular mass and cardiomyocyte dimensions (2,3,28,29) or did not induce any effects (16,18). However, 10-20% improvements in V O 2 max and work economy had been demonstrated (16,30).…”
mentioning
confidence: 94%
“…The better response of the stressed rats may be due to increase in myofilament calcium-sensitivity 31,32 and increased sarcoplasmic reticulum calcium uptake 33,34 induced by chronic stress. These postulations are extrapolated from a previous study 35 that observed better inotropic response to calcium in rats subjected to exercise training.…”
Section: Discussionmentioning
confidence: 99%